Assessing Elementary Teachers Knowledge and Readiness of Inclusive Education in District of Santa Fe - Olaya, Jodel (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study assessed the knowledge and readiness of elementary teachers in the District of Santa Fe, Division of Leyte, toward the implementation of inclusive education. Grounded in inclusive education principles that emphasize equality, learner participation, and the reduction of barriers to learning, the study focused on determining teachers’ level of knowledge, level of readiness, and the relationship between these two variables. A correlational research design was used, involving 30 elementary teacher-respondents selected through multistage cluster sampling. Data were gathered using a structured survey questionnaire with sections on teachers’ knowledge and readiness for inclusive education, rated through a four-point Likert scale. The instrument was validated through expert evaluation, and the data were analyzed using weighted mean and Pearson Product-Moment Correlation Coefficient at the 0.05 level of significance. Findings showed that teachers had a high level of knowledge on inclusive education, with an overall weighted mean of 3.20, and a very high level of readiness, with an overall weighted mean of 3.55. However, gaps were noted in teachers’ knowledge of disability categories, confidence in identifying learners with special educational needs, access to resources, and perceived administrative support. The correlation analysis revealed a very weak negative and non-significant relationship between knowledge and readiness, with r = −0.025 and p = 0.465. The study concludes that while teachers are generally knowledgeable and prepared, knowledge alone does not necessarily translate into practical readiness. The study supports SDG 4, Quality Education, by promoting inclusive and equitable learning opportunities for all learners. Its sustainability impact lies in strengthening educational, institutional, and community support systems for inclusive education in rural school contexts.